Sources of leader's legitimacy, an experiment - Tan, Melody (Nanyang Technological University, 2023)
Recent research has highlighted the importance of legitimacy, in determining the impact of leaders on their followers. It is believed that various sources of legitimacy can influence a leader’s effectiveness in managing and motivating their team. This study aims to investigate how different legitimacy types, namely institutional and personal legitimacy, can affect cooperation among followers and whether leader selection procedure can improve cooperation. Subjects were engaged in a public goods game, which examined how various legitimacy types and leader selection mechanisms influence outcomes. Leaders were chosen through members’ vote, previous leaders’ vote, or random selection at the beginning of each round. Once selected, leaders would choose a message from a list that reflects either the institution’s or personal power before members contributed to the game.